Comparison of Blood Counts and Markers of Inflammation and Coagulation in Patients With and Without COVID-19 Presenting to the Emergency Department in Seattle, WA. Issue 2 (21st June 2021) - Chandler, Christopher M; Reid, Molly C; Cherian, Sindhu; Sabath, Daniel E; Edlefsen, Kerstin L
Abstract: Objectives: We compared complete blood count (CBC) with differential and markers of inflammation and coagulation in patients with and without coronavirus disease 2019 (COVID-19) presenting to emergency departments in Seattle, WA. Methods: We reviewed laboratory values for 1 week following each COVID-19 test for adult patients who received a standard severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse transcription polymerase chain reaction (RT-PCR) test before April 13, 2020. Results were compared by COVID-19 status and clinical course. Results: In total 1, 027 patients met inclusion criteria. Patients with COVID-19 (n = 155) had lower leukocytes (P < .0001), lymphocytes (P < .0001), platelets (P < .0001), and higher hemoglobin (P = .0140) than those without, but absolute differences were small. Serum albumin was lower in patients with COVID-19 (P < .0001) and serum albumin, neutrophil to lymphocyte ratio (NLR), and red cell distribution width (RDW) were each associated with disease severity. NLR did not differ between patients with COVID-19 and those without (P = .8012). Conclusions: Patients with COVID-19 had modestly lower leukocyte, lymphocyte, and platelet counts and higher hemoglobin values than patients without COVID-19. The NLR, serum albumin, and RDW varied with disease severity, regardless of COVID-19 status.